Giant electron-hole transport asymmetry in ultra-short quantum transistors - A. C. McRae (Nature Portfolio, 2017)
By utilizing electron-hole asymmetry in ultra-short single-walled carbon nanotube (SWCNT) transistors, McRaeet al., develop ‘two-in-one’ SWCNT quantum devices that can switch from behaving as quantum-dot transistors for holes to quantum buses for electrons by changing the transistor’s gate voltage